The Influence of the Campus Teaching Program on the Mathematical Literacy Ability of Parepare Students - Abdul Rahman; Arifin Arifin (Universitas Muhammadiyah Enrekang, 2024)
This experimental research aims to determine the effect of the campus teaching program on students' mathematical literacy abilities in Parepare. The population of this study were students of junior high schools in Parepare. The sample in this study is one of the beneficiaries of the teaching campus program, namely SMP AL Badar, Parepare using the Purposive Sampling technique. The research data was obtained using an instrument in the form of an essay test consisting of 3 questions. The data analysis technique used is descriptive statistical data analysis and inferential statistical data analysis. The results of the descriptive statistical analysis of the pretest results showed that the average mathematical literacy ability for the experimental group was 52.50 and the control group was 53.15. After receiving the benefits of the teaching campus program for the experimental group, the average score for students' mathematical literacy was 73.62 and that of the control class was 66.38. The results of inferential statistical analysis based on the independent sample test show that the sig. 0.785 > α. So H1 is accepted and H0 is rejected. it can be concluded that there is a positive influence of the campus teaching program on students' mathematical literacy skills in Parepare.